Design fabrication and Novel Calibration Techniques for Heat Transfer Gauges During Short-Duration Transient Measurement - Kumar, Rakesh (My University, 2014)
Measurement of transient surface temperature and heat flux is the major requirement in many scientific and engineering applications such as design of combustion chamber in internal combustion engines, design of systems/sub-systems like heat exchanger, steam/gas turbines and thermal protection systems for high speed flight vehicles. In each of the cases, the technique used for accurate heat fluxes measurement must be suited for transient conditions and must have a fast enough response time to trace variations caused by rapidly change in flow conditions. Moreover, there are certain practical situations in which it may not be feasible to keep the thermal sensors exactly on the surface rather they are measured at some interior points inside the medium. For any case, the surface heat fluxes are mostly predicted from the measured temperature histories. The surface heat transfer mapping technique uses very fast response sensors to capture the transient temperature variations and subsequently, the heat fluxes are obtained through appropriate heat transfer modelling. Thus, the estimation of proper temporal nature of heat load and precise quantification of heat fluxes are the roots of a typical temperature sensor during transient measurements. Thin film gauges (TFGs) and coaxial thermocouples are resistance temperature detector sensors, suitable in measuring highly transient surface temperatures because the response time of these sensors are in the range of microseconds. The transient measurement of temperatures is usually performed by mounting these sensors embedded inside the heated material surface. The surface heat fluxes are then estimated from the measured temperature history through one-dimensional analytical heat transfer modelling. Thin film heat transfer gauges are generally made out of temperature sensitive materials (platinum/nickel/silver) and deposited on an insulated substrate material (pyrex/quartz/macor). The temperature sensing materials are normally viii available in the form of paste/ink form and are used to prepare thin film on the substrate material. Moreover, their resistances are extremely sensitive to temperature that varies linearly with temperature.
Sahoo, Niranjan
Keywords: MECHANICAL ENGINEERING; MECHANICAL ENGINEERING